Analisis Pemborosan Menggunakan Waste Assessment Model (WAM) pada Proses Penyediaan Unit pada Distributor Perdagangan - Marsudin, Ahmad; Kholil, Muhammad (Fakultas Teknik Universitas Tulang Bawang, 2025)
The distribution company for agricultural, construction, and infrastructure equipment is experiencing delays in the supply of units, which can lead to resource depletion and potentially cause customer loss. Supply delays represent a form of waste that must be eliminated. This study aims to identify the causes of the delays using the waste assessment model approach. Data was collected through questionnaires and interviews conducted with assembly supervisors and team leaders. Data processing utilized the waste assessment model, which consists of the waste relationship matrix (WRM) and the waste assessment questionnaire (WAQ). The WRM results indicated a strong correlation between defects, processes, overproduction, and inventory, while the WAQ results showed the largest waste occurred in inventory, motion, and waiting. The highest waste in this study was identified as defects, inventory, and motion. The results of this research are expected to provide effective recommendations to reduce supply delays and improve the company's operational efficiency. Consequently, the company can maintain and even enhance customer satisfaction, as well as optimize the distribution process of agricultural, construction, and infrastructure equipment. Keywords: Distributor, Supply Delays, Waste, WAM